Variations in depressive affects due to differences in gender and residence (Journal of Life and Earth Science, 2011)
The study explores the phenomenon of depression as a function of gender and residence. A total of 40 respondents constituted the sample. The age of the respondents ranged from 40-65 years. A 2×2 factorial design representing two levels of gender (Male/Female) and two levels of residential background (Urban/Rural) was used. Two hypotheses were formulated. The first hypothesis states that female would exhibit more depressive symptoms than the males. The second hypothesis states that respondents with rural residential background would exhibit more depressive symptoms than the respondents with urban residential background. The statistical technique of analysis of variance (ANOVA) was used for the analysis of data. The results provided empirical support to the second hypothesis. It was found that respondents with rural residential background expressed significantly more depressive symptoms than the respondents with urban residential background. Key words: Depressive affect; self-esteem; adolescence; brain chemistry; mental health. DOI: 10.3329/jles.v2i2.7498 J. Life Earth Sci., Vol. 2(2) 51-55, 2007